The Effect of Fear on Purchase Decisions Food and Beverages through The Online Food Delivery Application during The Covid-19 Pandemic - Ulhaq, Reyna Nadhya; Munandar, Jono M; Rifin, Amzul (Jurnal Manajemen, 2023)
Online food delivery app adoption is an alternative marketing strategy for food retailing SMEs during the Covid-19 pandemic. One of the impacts of the covid-19 pandemic was the existence of psychological disorders, namely the fear of covid-19. Fear of covid-19 contributed to determining consumer behavior. This study aimed to analyze the effect of fear on purchase intention using online food delivery apps and the effect of purchase intention on purchase decisions through online food delivery apps. The research was conducted on July 2020 in Jabodetabek as Indonesia's city with an economic center. The sample used in this study was 100 samples taken by the purposive sampling method. The data were processed using SEM-PLS. This study examined three variables namely fear, purchase intention, and purchase decision. The results showed that some sub-variable of fear positively affects purchase intentions through online food delivery apps. The variables were triggers of fear, coping strategies, and functional impairment. In addition, during the Covid-19 pandemic, consumer purchase intentions significantly affected purchase decisions through online food delivery apps. The existence of the COVID-19 pandemic does not only have a psychological impact in the form of fear, but it also causes anxiety and worry. Further research can examine the effect of anxiety and worry to purchase intention and purchase decision through online food delivery apps.